The Influence of Accounting Profits, Cash Flow Statements and Company Size on Stock Returns in Manufacturing Companies - Diah Firani (Jurnal Manajemen Bisnis Eka Prasetya, 2024)
This research aims to investigate the impact of several factors on stock returns in manufacturing companies. The research employs a quantitative associative research method and utilizes a multiple regression sampling technique. The sample consists of 15 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2022, totaling 60 data points from annual financial reports. The partial results of the research reveal that accounting profit and operating cash flow do not have a significant impact on stock returns. However, investment cash flow has a significant effect on stock returns, while financing cash flow and company size do not have a significant influence on stock returns. Overall, the research findings indicate that simultaneously, accounting profit, operating cash flow, investment cash flow, financing cash flow, and company size have a significant impact on stock returns in manufacturing companies. This study provides valuable insights into the factors influencing the stock performance of manufacturing companies and can serve as a guide for investors and decision-makers in managing their portfolios